Housing purchase decision: the variations type of housing development in Malaysia - Hassan, Mohammad Mujaheed; Ahmad, Nobaya; Hashim, Ahmad Hariza (Human Resource Management Academic Research Society, 2021)
This article aims to review the variation of house development in Malaysia. Currently, several categories of house property are available in Malaysia, which commonly includes terraces, bungalows, apartment, flat, condominium, and semi-D among others. The cost of property varies based on its category, size, and placement. The selling of a developing property is under the management of the Housing Development (Control and Licensing) Act 1966 (“HDA”) for accommodation. Furthermore, HDA consists of some degrees of protection for homebuyers. The National Land Code 1965 (NLC) governs the tenure and land ownership in Peninsular Malaysia, and it was effective on 1st January 1965. Moreover, Sabah and Sarawak have enacted particular groups of rules, namely the Sabah Land Ordinance and the Sarawak Land Code, respectively. Notably, the variety of property names are essential as it contributes to various entitlements. Under the Torrens system in Malaysia, the individual with a position of the proprietor of the property name is perceived as the legal owner. Therefore, it is encouraged that the homebuyer performs a name search at the end of the land registry or office for verification regarding the details of the property name before purchasing it. Property names include the master, individual, strata, Bumiputera reserve, commercial, or residential. In the case of property tenure, it may either be freehold or leasehold. Homebuyers need to understand the various types of housing development in Malaysia for their security and protection.